Two new Palaearctic species of moth flies (Diptera, Psychodidae, Psychodinae) from the Caucasus Mts. - Ježek, Jan; Oboňa, Jozef; Manko, Peter (Zootaxa, 2021)
Psychodid specimens were sorted from samples collected during fieldwork in areas in and around the Caucasus Mountains in 2019. Thornburghiella montana sp. nov. (from Georgia) and Pericoma inopinata sp. nov. (from Azerbaijan and Georgia) are described. Differential diagnoses are given and diagnostic characters illustrated.